KODIFIKASI HADIS PADA MASA KHALIFAH UMAR BIN ABDUL AZIZ - Alifia Melfitara; Romlah Askar; Abdul Gofur (Ilma Jurnal Pendidikan Islam, 2025)
The science of hadith is a discipline that studies hadith, including narrators, sanad, and everything related to hadith. Hadith is the second source of law after the Qur'an. Hadith is everything that is based on the Prophet Muhammad SAW, whether it is actions, words, or decrees. The very important position of the Prophet's hadith in Islam makes Muslims continue to strive to preserve it. In the first century of Hijri, a great idea emerged from Khalifah Umar bin Abdul Aziz to collect the hadiths of the Prophet in writing. This idea received a positive response from the scholars, so that from then on the process of collecting and codifying hadith began. With the support of the government and the sincerity of the scholars in preserving this second source of Islamic teachings, the collection of hadith went smoothly. Furthermore, in the second, third, and fourth centuries of Hijri, the codification of hadith was carried out massively by great scholars, so that hadith literature developed rapidly and systematically. This article will discuss the history of the development of hadith science and its codification. The method that the author used in writing this article is the library research method by collecting data in the form of journals, books, and other documents related to hadith. The purpose of writing this article is to find out the codification of hadith during the caliphate of Umar bin Abdul Aziz. The benefits of the research in this article are to find out the codification of hadith and what happened regarding hadith during the time of Umar bin Abdul Aziz. The results of this study are that the codification of hadith was carried out during the time of Umar bin Abdul Aziz because he was worried that hadith would be lost and the spread of fake hadith, so steps were needed to maintain the authenticity and authenticity of hadith